Serological and Molecular Survey of Brucella Species in Owners and Their Dogs Living on Island and Mainland Seashore Areas of Brazil - Costa Barros, Noelia Layslla [UNESP]; Ribeiro, Matheus Lopes [UNESP]; Freitas, Aaronson Ramathan; Delai, Ruana Renostro; Kmetiuk, Louise Bach; Teixeira, Wanderson Sirley Reis [UNESP]; Appolinario, Camila Michele [UNESP]; Pimpão, Claudia Turra; Ponsart, Claire; Vicente, Acacia Ferreira; Biondo, Alexander Welker; Megid, Jane [UNESP] (SAGE Publications, 2024)
Background: Although Brucella abortus, Brucella suis, and Brucella canis may infect humans and dogs worldwide, no study to date has assessed and compared owners and their dogs between island and mainland seashore areas. Materials and Methods: Accordingly, the study herein has applied serological tests, including Microplate Agglutination Test with 2-Mercaptoethanol, immunochromatographic assay, and Rose Bengal Test, and a Brucella genus-specific PCR assay to 195 owners and their 148 dogs living on 1 mainland seashore area and three nearby oceanic islands of southern Brazil. Results: No seropositivity to B. abortus and B. suis was detected in owner or dog sera. Anti-B. canis seropositivity was observed in 3/148 (2.0%) dogs, but no owner sample was seropositive to B. canis. In addition, all blood samples from both owners and dogs were negative on Brucella genus-specific PCR assay. Conclusions: The seropositive dogs were not related and lived on the seashore mainland area of Guaraqueçaba city. The absence of seropositivity on the islands and the low seropositivity on the seashore mainland could be attributed to geographic isolation, and suggest the low impact of the disease in the region. Despite being a zoonotic disease, brucellosis by B. canis is not included in the National Program for Control and Eradication of Brucellosis, and its diagnosis and notification are not mandatory. The presence of seropositive dogs highlights the risk to human health and the importance of epidemiological surveillance actions in the region, as well as the need for the implantation of preventive measures to avoid the transmission of the pathogen.
Keywords: Brucella abortus; Brucella canis; brucellosis; public health; zoonosis